Executive Committee Minutes 2022-04-21 - Academic Senate:::::::::
Approval of Agenda - Approved. Minutes of 4/7/22 - Approved. Chair Report. Statewide Senators Report. Vice Chair Report. Vice President of Student Affairs Report. Revision to the Human Subjects Research Policy - Approved for Senate Agenda. Provost Report. Resolution of No Confidence in President Sakaki - Approved for Senate agenda. Name change for Engineering Department - Approved an info item for Senate. Post tenure review discussion. Equitable Access to Learning Materials presentation. Student Representative Report. Senate Agenda - Approved.